INTEGRASI AGAMA DAN ILMU PENGETAHUAN (SAINS): (Berdasarkan Kajian Epistemologi Bayani, Irfani dan Burhani) - Syafrudin (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2020)
Islam is a religion which teaches that science and religion are interrelated and complementary. Religion is a source of knowledge and knowledge is a means of applying everything contained in religious teachings. Religion and science will mutually strengthen and synergize so as to produce individuals who are obedient in religion and at the forefront of science. But lately what has happened is that general science (science) is growing rapidly while Islamic science has experienced a decline, which in the end has emerged a dichotomy between the two fields of science. Not only here, but also the secularization of science. However, this secularization of knowledge was challenged by the Church. Punishment for scientists who dare to differ from the views of the Church has triggered the birth of science that separates itself from religious doctrine. This condition motivates Muslim intellectuals to strive to reintegrate science and religion. The idea of ​​the integration or Islamization of science today carried out by Muslim intellectuals cannot be separated from religious awareness. In totality amidst the bustling global world which is full of advances in science and technology. Knowledge that is actually the result of human reading of the verses of Allah SWT, loses its spiritual dimension, so knowledge or science that has nothing to do with religion develops.